REGULASI ADMINISTRASI KESEHATAN DALAM RANGKA MENINGKATKAN KEADILAN AKSES LAYANAN KESEHATAN - Gunawan Widjaja (ADMIN: Jurnal Administrasi Negara, 2025)
Health administration regulations are crucial in efforts to improve equitable access to health services for all segments of society. Effective regulations can reduce disparities in access to services, especially for vulnerable groups such as low-income communities and those in remote areas. Transparency and good governance of these regulations also enhance public trust and ensure optimal utilisation of resources. Additionally, the integration of health technology and patient data digitalisation can support administrative efficiency and reduce common barriers. Regular evaluation and development of regulations are necessary to adapt to the evolving needs of society and address modern health challenges. Thus, effective health administration regulations not only improve equitable access to services but also support the achievement of a sustainable and equitable health system